Ta có:
ab + ba = 121
=> (10a + b) + (10b + a) = 121
=> 10a + b + 10b + a = 121
=> 11a + 11b = 121
=> 11.(a + b) = 121
=> a + b = 121 : 11 = 11 (1)
ab - ba = 45
=> (10a + b) - (10b + a) = 45
=> 10a + b - 10b - a = 45
=> 9a - 9b = 45
=> 9.(a - b) = 45
=> a - b = 45 : 9 = 5 (2)
Từ (1) và (2) => b = (11 - 5) : 2 = 3; a = 3 + 5 = 8
Vậy a = 8; b = 3
Ta có:
ab + ba = 121
=> (10a + b) + (10b + a) = 121
=> 10a + b + 10b + a = 121
=> 11a + 11b = 121
=> 11.(a + b) = 121
=> a + b = 121 : 11 = 11 (1)
ab - ba = 45
=> (10a + b) - (10b + a) = 45
=> 10a + b - 10b - a = 45
=> 9a - 9b = 45
=> 9.(a - b) = 45
=> a - b = 45 : 9 = 5 (2)
Từ (1) và (2) => b = (11 - 5) : 2 = 3; a = 3 + 5 = 8
Vậy a = 8; b = 3
Ta có:
ab + ba = 121
=> (10a + b) + (10b + a) = 121
=> 10a + b + 10b + a = 121
=> 11a + 11b = 121
=> 11.(a + b) = 121
=> a + b = 121 : 11 = 11 (1)
ab - ba = 45
=> (10a + b) - (10b + a) = 45
=> 10a + b - 10b - a = 45
=> 9a - 9b = 45
=> 9.(a - b) = 45
=> a - b = 45 : 9 = 5 (2)
Từ (1) và (2) => b = (11 - 5) : 2 = 3; a = 3 + 5 = 8
Vậy a = 8; b = 3